PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA SMARTPHONE MADE IN CHINA DI KECAMATAN CIKUPA KABUPATEN TANGERANG - Lita Novianti; Lod Sulivyo (JURNAL CAFETARIA, 2021)
This study aims to analyze and find out if there is an influence of Product Quality and Promotion on Smartphone Purchase Decisions Made in China in Cikupa Subdistrict, Tangerang Regency. Samples used in this study as many as 100 respondents and sampling using purposive sampling techniques. In this study, the analysis was conducted using the help of SPSS Software Application Version 23. While the data testing techniques conducted in this study are validity test, reliability test, normality test, partial correlation analysis, coefficient of determination, multiple linear test, and hypothesis test (t test and f test). based on the results of partial correlation analysis can be known the value of the influence of variable correlation of Product Quality and Promotion on Purchasing Decisions of 0.533 and 0.648, respectively. While the results of multiple correlation analysis shows the result of the value R2 ( R Square) = 50.8%. This indicates that the Quality of Products (X1) and Promotions (X2) simultaneously had a significant effect on Purchasing Decisions (Y) with a Coefficient of Determination value of 49.8% while the remaining 50.2% was influenced by other factors not studied by researchers.